[1,2-Bis(1H-benzimidazol-2-yl-kappa N-3)ethane]dichloridozinc(II) - Zhou, Y.L.; Zeng, M.H.; Ng, S.W. (International Union of Crystallography, 2010)
The title compound, [ZnCl2(C16H14N4)], crystallizes with two molecules in the asymmetric unit. The Zn-II atoms show distorted tetrahedral coordination environments. Adjacent molecules are linked by N-H center dot center dot center dot Cl hydrogen bonds, forming a three-dimensional network.